You are on page 1of 1

Theorem: Let A and B be matrices.

(AB)T =
B T AT .
Proof:
First observe that the ij entry of AB can be written as
n
X
(AB)ij =
aik bkj .
k=1

Furthermore, if we transpose a matrix we switch
the rows and the columns. These facts together
mean that we can write
(AB)T 

ij

= (AB)ji =

n
X

ajk bki

k=1

and
(B T AT )ij =

n
X

(B T )ik (AT )kj =

k=1

n
X

bki ajk .

k=1

From here is is clear that the ij entry of the left
and right sides are equal. Therefore the matrices
are equal.

1